PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KERJA KARYAWAN TOSERBA BERKAH JAYA CIPARI - Ernawati (AmaNU: Jurnal Manajemen dan Ekonomi, 2023)
This research is a survey research on the work motivation of the employees of the Berkah Jaya Cipari Department Store in Cilacap. This study takes the title:"The Influence of Reward and Punishment on Employee Motivation at the Berkah Jaya Cipari Department Store". The aim of this study was to determine the effect of reward and punishment on employee motivation. The population in this study were all employees of the Jaya Cipari Berkah Department Store.The implication of the conclusions above is that in an effort to increase customer satisfaction, the management of the Jaya Cipari Berkah Department Store is expected to pay attention to employee conditions such as work motivation needs. Companies need to pay attention to indicators that affect employee motivation and realized according to company policy. Reward factors that influence employees can also be considered as a form of work motivation given. The firmness in giving punishment to the employees of the Berkah Jaya Cipari Department Store also needs to be improved.